A sheet monocrystal sodium iron pyrophosphate positive electrode material, a preparation method and application thereof
Patent Information
- Application Number
- CN202611220702.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-16
AI Technical Summary
然而,熔盐法在NFPP正极材料应用时,NFPP的晶体结构对反应温度和熔盐组分的兼容性要求较高,难以直接沿用其它钠离子电池正极材料的熔盐体系
本发明首次采用低熔点复合熔盐体系辅助NFPP的熔盐法合成,开辟了NFPP片状单晶材料制备的新技术路径,具有独创性。传统的熔盐法常采用单一熔盐(如NaCl)或二元共晶熔盐(如NaCl-KCl),但其熔点较高(NaCl单一熔盐熔点为801℃)或与NFPP前驱体的兼容性差。本发明通过设计NaCl-KCl-Na2SO4三元复合熔盐体系,通过优化三者的摩尔比(优选50:35:15)使其共晶熔点降至530~620℃,远低于传统熔盐熔点。这一独特设计不仅降低了合成温度窗口、节省了能耗,更重要的是在NFPP的稳定温区(600~700 ℃)实现了完全液化的熔盐介质,避免了高温导致的NFPP晶相分解和Fe2+氧化。
Smart Images

Figure CN122918689A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery materials technology, and in particular to a sheet-like single-crystal sodium iron phosphate pyrophosphate cathode material, its preparation method, and its application. Background Technology
[0002] Sodium-ion batteries are considered a promising alternative or supplementary energy storage system to lithium-ion batteries due to their abundant resources, low cost, and wide distribution. Sodium iron phosphate pyrophosphate (Na4Fe3(PO4)2P2O7, abbreviated as NFPP), as an iron-based polyanionic cathode material, contains phosphate ions (PO4) in its structure. 3- ) and pyrophosphate (P2O7) 4- It has two anion units to form an open three-dimensional sodium ion diffusion channel, which has the advantages of high specific capacity (theoretical specific capacity 129mAh / g), low preparation cost, good cycle performance and good thermal stability. It is considered to be one of the most promising sodium-ion battery cathode materials.
[0003] However, NFPP materials suffer from inherent defects such as low electronic conductivity and slow ion diffusion kinetics, which severely restricts further improvements in their rate performance and energy density. Studies have shown that preparing NFPP into single crystals and controlling its lamellar morphology can increase compaction density, effectively eliminate grain boundary impedance within polycrystalline particles, and shorten the diffusion path of sodium ions, significantly improving the material's sodium storage capacity. Existing technologies suffer from common technical bottlenecks such as narrow process windows, poor morphology controllability, and difficulty in balancing lamellar morphology with single crystal purity.
[0004] Molten salt synthesis, as an emerging material synthesis method, has attracted widespread attention in the field of sodium-ion battery cathode materials in recent years. Its core principle is to significantly improve the solubility and diffusion rate of reactants by selecting appropriate molten salt components and sintering conditions, utilizing the liquid reaction medium formed by low-melting-point molten salt at high temperatures. This promotes anisotropic growth and single-crystal formation of grains, resulting in single-crystal particles with preferred crystal orientations. However, when applying molten salt synthesis to NFPP cathode materials, the crystal structure of NFPP has high compatibility requirements regarding reaction temperature and molten salt components, making it difficult to directly use the molten salt systems of other sodium-ion battery cathode materials. Summary of the Invention
[0005] Based on this, the purpose of this invention is to provide a sheet-like single-crystal sodium iron phosphate pyrophosphate cathode material, its preparation method and application. By utilizing the liquid reaction medium formed by low-melting-point composite molten salt at high temperature, the anisotropic growth of grains is promoted through dissolution-precipitation, thereby achieving the controllable preparation of sheet-like single-crystal NFPP in one step.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: This invention provides a method for preparing a sheet-like single-crystal sodium iron phosphate pyrophosphate cathode material, which includes the following steps: mixing a sodium iron phosphate pyrophosphate precursor with a composite molten salt, calcining, and post-processing to obtain a sheet-like single-crystal sodium iron phosphate pyrophosphate cathode material; wherein the composite molten salt includes sodium chloride, potassium chloride, and sodium sulfate, and the eutectic melting point is 530~620℃.
[0007] This invention utilizes a liquid reaction medium formed by a low-melting-point composite molten salt at high temperature to promote the anisotropic growth of iron phosphate pyrophosphate grains on various crystal planes through a dissolution-precipitation mechanism, effectively inhibiting particle agglomeration and achieving controllable preparation of plate-like single-crystal NFPP in one step. The molten salt system of this invention is recyclable and reusable, and the preparation process does not require complex template removal steps, making the process simple, low-cost, and suitable for large-scale production.
[0008] As a further improvement to the above-described scheme of the present invention, the molar ratio of sodium chloride (NaCl), potassium chloride (KCl), and sodium sulfate (Na2SO4) in the composite molten salt is (40~60):(25~40):(5~15). More preferably, the molar ratio of sodium chloride, potassium chloride, and sodium sulfate is NaCl:KCl:Na2SO4=50:35:15.
[0009] As a further improvement of the above-mentioned solution of the present invention, the sodium iron phosphate pyrophosphate precursor includes a sodium source, an iron source and a phosphorus source, and the mass ratio of the sodium iron phosphate pyrophosphate precursor to the composite molten salt is 1:(0.5~5); preferably 1:(1~3).
[0010] As a further improvement to the above-mentioned scheme of the present invention, the sodium source is selected from at least one of sodium carbonate, sodium acetate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium oxalate, and sodium nitrate; the iron source is selected from at least one of ferric nitrate, ferric phosphate, ferrous sulfate, ferrous oxalate, and ferric fluoride; and the phosphorus source is selected from at least one of ammonium dihydrogen phosphate, orthophosphoric acid, diammonium hydrogen phosphate, and phosphoric acid.
[0011] As a further improvement to the above-mentioned solution of the present invention, the calcination is carried out under a protective atmosphere, with the temperature increased to 550-750°C at a heating rate of 1-5°C / min and held for 2-8 hours; preferably, the temperature is increased to 600-700°C and held for 3-6 hours.
[0012] As a further improvement to the above-mentioned solution of the present invention, the post-processing includes: washing several times alternately with deionized water and anhydrous ethanol until chloride ions and sulfate ions are no longer detectable in the washing solution, and then vacuum drying.
[0013] As a further improvement to the above-mentioned solution of the present invention, the vacuum drying temperature is 80~120℃ and the drying time is 6~12h.
[0014] The present invention also provides a sheet-like single-crystal sodium iron phosphate pyrophosphate cathode material, which is prepared by the preparation method described above.
[0015] As a further improvement to the above-described scheme of the present invention, the positive electrode material has the chemical formula Na4Fe3(PO4)2P2O7, exhibits a plate-like single crystal morphology, has a plate thickness of 10~50 nanometers, and a compaction density of 2.5~2.8 g / cm³. 3 .
[0016] The present invention also provides an application of the sheet-like single-crystal sodium iron pyrophosphate cathode material prepared by the preparation method described above in the cathode of a sodium battery.
[0017] Compared with the prior art, the present invention has the following beneficial effects: This invention is the first to employ a low-melting-point composite molten salt system to assist in the molten salt synthesis of NFPP, opening up a new technological pathway for the preparation of NFPP sheet-like single-crystal materials, demonstrating originality. Traditional molten salt methods often use single molten salts (such as NaCl) or binary eutectic molten salts (such as NaCl-KCl), but these have high melting points (NaCl alone has a melting point of 801℃) or poor compatibility with NFPP precursors. This invention designs a NaCl-KCl-Na2SO4 ternary composite molten salt system, optimizing the molar ratio of the three components (preferably 50:35:15) to lower its eutectic melting point to 530-620℃, far below the melting point of traditional molten salts. This unique design not only reduces the synthesis temperature window and saves energy, but more importantly, it achieves a completely liquefied molten salt medium within the stable temperature range of NFPP (600-700℃), avoiding the decomposition of the NFPP crystal phase and Fe2+ caused by high temperatures. 2+ Oxidation.
[0018] The NaCl-KCl-Na2SO composite molten salt used in this invention can be recovered through evaporation and crystallization after washing, enabling recycling and significantly reducing production costs and waste emissions. Furthermore, the molten salt components are all common, non-toxic, and non-corrosive inorganic salts, making it environmentally friendly.
[0019] This invention utilizes a high-temperature molten salt liquid medium where reaction precursors (sodium, iron, and phosphorus sources) are dissolved by the molten salt to form a homogeneous liquid phase environment. With the uniform diffusion and ion migration of the molten salt, NFPP crystal nuclei preferentially nucleate and grow on specific crystal planes within the molten salt liquid phase. The dissolution-precipitation process provides the grains with sufficient spatial freedom and material supply, reducing grain boundary defects and particle agglomeration, thus achieving controllable preparation of plate-like single crystals in one step.
[0020] Compared with the traditional soft template method, the molten salt-assisted synthesis method of the present invention does not require the introduction of complex organic template agents, nor does it require a wet post-treatment step for template removal. The molten salt medium can be removed simply by washing with water / alcohol, which simplifies the process and reduces costs. Attached Figure Description
[0021] Figure 1 for Figure 1 Transmission electron microscope images of sodium iron phosphate pyrophosphate cathode materials prepared in Example 1 and Comparative Example 1; Figure 2 The first charge-discharge curves of the sodium iron phosphate pyrophosphate cathode materials prepared in Example 1 and Comparative Examples 1-3 at 0.1 C are shown. Figure 3 The charge-discharge curves of the sodium iron phosphate pyrophosphate cathode materials prepared in Examples 1-3 and Comparative Example 1 at 5 C are shown. Detailed Implementation
[0022] To facilitate understanding of the present invention, a more comprehensive description will be given below with reference to specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of the present invention.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.
[0024] Example 1 This embodiment proposes a method for preparing a sheet-like single-crystal sodium iron phosphate pyrophosphate cathode material, which includes the following steps: S1. Weigh out NaCl, KCl, and Na2SO4 in a molar ratio of 50:35:15 and grind them thoroughly in an agate mortar until they are evenly mixed to obtain a low-melting-point composite molten salt (the measured melting point is about 560℃). S2. Weigh out 2.12 g (0.02 mol) sodium carbonate (Na2CO3), 4.48 g (0.03 mol) ferric phosphate (FePO4), and 4.60 g (0.04 mol) ammonium dihydrogen phosphate (NH4H2PO4) according to the NFPP stoichiometric ratio Na:Fe:P = 4:3:4 to obtain sodium iron phosphate pyrophosphate precursor. Mix the low-melting-point composite molten salt prepared in step S1 with the sodium iron phosphate pyrophosphate precursor at a mass ratio of 2:1, that is, add about 22.4 g of low-melting-point composite molten salt to the above sodium iron phosphate pyrophosphate precursor, and add 2.0 g of glucose as a carbon source. Grind and mix thoroughly in a mortar for 30 minutes to obtain a homogeneous mixture. S3. Spread the mixture obtained in step S2 evenly in an alumina crucible, place it in a tube furnace, and introduce high-purity nitrogen gas (purity ≥99.999%) at a flow rate of 500 mL / min to ensure that the calcination process is carried out in an inert atmosphere. Raise the furnace temperature to 650℃ at a heating rate of 3℃ / min and hold at 650℃ for 8 hours. After the holding period, allow it to cool naturally to room temperature under nitrogen gas protection. S4. Transfer the sintered product obtained in step S3 to a beaker and wash it alternately with deionized water and anhydrous ethanol until chloride ions are undetectable with AgNO3 solution and sulfate ions are undetectable with BaCl2 solution in the washing solution. Dry the washed product in a vacuum drying oven at 100℃ for 8 hours to obtain the sheet-like single-crystal NFPP cathode material, denoted as NFPP-M1.
[0025] Example 2 This embodiment proposes a method for preparing a sheet-like single-crystal sodium iron phosphate pyrophosphate cathode material, which includes the following steps: S1. Weigh out NaCl:KCl:Na2SO4 according to a molar ratio of 45:40:15 and grind and mix them thoroughly in an agate mortar to obtain a low melting point composite molten salt (the measured melting point is about 585℃). S2. Weigh out the following ingredients according to the stoichiometric ratio of NFPP: Na:Fe:P = 4:3:4: 3.28 g (0.04 mol) sodium acetate (CH3COONa), 5.40 g (0.03 mol, equivalent to 0.03 mol Fe) ferrous oxalate (FeC2O4·2H2O), and 4.60 g (0.04 mol) orthophosphoric acid (H3PO4, 85%) to obtain sodium iron phosphate pyrophosphate precursor. Mix the low-melting-point composite molten salt prepared in step S1 with the sodium iron phosphate pyrophosphate precursor at a mass ratio of 1.5:1, and add 2.0 g of glucose as a carbon source. Grind and mix thoroughly in a mortar for 30 minutes to obtain a homogeneous mixture. S3. Spread the mixture obtained in step S2 evenly in an alumina crucible, place it in a tube furnace, and introduce high-purity argon gas (purity ≥99.999%) at a flow rate of 600 mL / min to ensure that the calcination process is carried out in an inert atmosphere. Raise the furnace temperature to 700℃ at a heating rate of 2℃ / min and hold at 700℃ for sintering for 5 hours. After the holding period, allow it to cool naturally to room temperature under the protection of the argon gas flow. S4. Transfer the sintered product obtained in step S3 to a beaker and wash it alternately with deionized water and anhydrous ethanol until chloride ions are undetectable with AgNO3 solution and sulfate ions are undetectable with BaCl2 solution in the washing solution. Dry the washed product in a vacuum drying oven at 100℃ for 8 hours to obtain the sheet-like single-crystal NFPP cathode material, denoted as NFPP-M2.
[0026] Example 3 This embodiment proposes a method for preparing a sheet-like single-crystal sodium iron phosphate pyrophosphate cathode material, which includes the following steps: S1. Weigh out NaCl:KCl:Na2SO4 according to a molar ratio of 55:30:15 and grind and mix thoroughly in an agate mortar to obtain a low melting point composite molten salt (the measured melting point is about 573℃). S2. Weigh out 6.24 g (0.04 mol) sodium dihydrogen phosphate (NaH2PO4·2H2O), 12.12 g (0.03 mol) ferric nitrate (Fe(NO3)3·9H2O), and 5.28 g (0.04 mol) diammonium hydrogen phosphate ((NH4)2HPO4) according to the NFPP stoichiometric ratio Na:Fe:P = 4:3:4 to obtain sodium iron phosphate pyrophosphate precursor. Mix the low-melting-point composite molten salt prepared in step S1 with the sodium iron phosphate pyrophosphate precursor at a mass ratio of 3:1, and add 2.0 g of glucose as a carbon source. Grind and mix thoroughly in a mortar for 30 minutes to obtain a homogeneous mixture. S3. Spread the mixture obtained in step S2 evenly in a corundum crucible, place it in a tube furnace, and introduce a nitrogen-argon mixture (by volume percentage: 80% Ar, 20% N2) at a flow rate of 400 mL / min to ensure that the calcination process is carried out in an inert atmosphere. Raise the furnace temperature to 680℃ at a heating rate of 4℃ / min and hold at 680℃ for sintering for 6 hours. After the holding period, allow it to cool naturally to room temperature under the protection of a nitrogen-hydrogen mixed gas flow. S4. Transfer the sintered product obtained in step S3 to a beaker and wash it alternately with deionized water and anhydrous ethanol until chloride ions are undetectable with AgNO3 solution and sulfate ions are undetectable with BaCl2 solution in the washing solution. Dry the washed product in a vacuum drying oven at 100℃ for 8 hours to obtain the sheet-like single-crystal NFPP cathode material, denoted as NFPP-M3.
[0027] Comparative Example 1 This comparative example presents a method for preparing sodium iron phosphate pyrophosphate cathode material (traditional solid-state method), which includes the following steps: 2.12 g of sodium carbonate, 4.48 g of iron phosphate, and 4.60 g of ammonium dihydrogen phosphate are weighed according to the stoichiometric ratio of NFPP Na:Fe:P = 4:3:4. 2.0 g of glucose is added as a carbon source, and the mixture is ground in a mortar for 30 minutes. The mixture is placed in a tube furnace, nitrogen gas is introduced, and the temperature is raised to 650°C at a heating rate of 3°C / min and held at 650°C for 8 hours. After natural cooling, conventional NFPP material is obtained, denoted as NFPP-C1.
[0028] Comparative Example 2 This comparative example presents a method for preparing sodium iron phosphate pyrophosphate cathode material, which includes the following steps: S1. Weigh out 2.12 g (0.02 mol) sodium carbonate (Na2CO3), 4.48 g (0.03 mol) ferric phosphate (FePO4), and 4.60 g (0.04 mol) ammonium dihydrogen phosphate (NH4H2PO4) according to the NFPP stoichiometric ratio Na:Fe:P = 4:3:4 to obtain sodium iron phosphate pyrophosphate precursor. Mix NaCl with the sodium iron phosphate pyrophosphate precursor at a mass ratio of 2:1, that is, add about 22.4 g of NaCl to the above sodium iron phosphate pyrophosphate precursor, and add 2.0 g of glucose as a carbon source. Grind and mix thoroughly in a mortar for 30 minutes to obtain a homogeneous mixture. S2. Spread the mixture obtained in step S1 evenly in an alumina crucible, place it in a tube furnace, and introduce high-purity nitrogen gas (purity ≥99.999%) at a flow rate of 500 mL / min to ensure that the calcination process is carried out in an inert atmosphere. Raise the furnace temperature to 650℃ at a heating rate of 3℃ / min and hold at 650℃ for 8 hours. After the holding period, allow it to cool naturally to room temperature under nitrogen protection. S3. Transfer the sintered product obtained in step S2 to a beaker and wash it alternately with deionized water and anhydrous ethanol until chloride ions are no longer detectable in the washing solution using AgNO3 solution. Dry the washed product in a vacuum drying oven at 100℃ for 8 hours to obtain the NFPP cathode material, denoted as NFPP-C2.
[0029] Comparative Example 3 This comparative example presents a method for preparing sodium iron phosphate pyrophosphate cathode material, which includes the following steps: S1. Weigh NaCl and KCl according to a molar ratio of 59:41 and grind them thoroughly in an agate mortar to obtain a composite molten salt (the measured melting point is about 658℃). S2. Weigh out 2.12 g (0.02 mol) sodium carbonate (Na2CO3), 4.48 g (0.03 mol) ferric phosphate (FePO4), and 4.60 g (0.04 mol) ammonium dihydrogen phosphate (NH4H2PO4) according to the NFPP stoichiometric ratio Na:Fe:P = 4:3:4 to obtain sodium iron phosphate pyrophosphate precursor. Mix the composite molten salt prepared in step S1 with the sodium iron phosphate pyrophosphate precursor at a mass ratio of 2:1, that is, add about 22.4 g of composite molten salt to the above sodium iron phosphate pyrophosphate precursor, and add 2.0 g of glucose as a carbon source. Grind and mix thoroughly in a mortar for 30 minutes to obtain a homogeneous mixture. S3. Spread the mixture obtained in step S2 evenly in an alumina crucible, place it in a tube furnace, and introduce high-purity nitrogen gas (purity ≥99.999%) at a flow rate of 500 mL / min to ensure that the calcination process is carried out in an inert atmosphere. Raise the furnace temperature to 650℃ at a heating rate of 3℃ / min and hold at 650℃ for 8 hours. After the holding period, allow it to cool naturally to room temperature under nitrogen gas protection. S4. Transfer the sintered product obtained in step S3 to a beaker and wash it alternately with deionized water and anhydrous ethanol until chloride ions are no longer detectable in the washing solution using AgNO3 solution. Dry the washed product in a vacuum drying oven at 100℃ for 8 hours to obtain the sheet-like single-crystal NFPP cathode material, denoted as NFPP-C3.
[0030] Test case (1) The sodium iron phosphate pyrophosphate cathode materials prepared in Example 1 and Comparative Example 1 were characterized to obtain the following results: Figure 1 The image shown is a transmission electron microscope image. From... Figure 1 As can be seen, Example 1 exhibits a distinct lamellar single-crystal morphology with a lamellar thickness of approximately 10 nm. This lamellar single-crystal morphology significantly improves the compactness of the cathode material compared to the particle morphology of Comparative Example 1, while also helping to shorten the sodium ion transport path and enhance structural stability during cycling.
[0031] (2) Compacted density test: A certain mass of positive electrode material powder is loaded into a specific mold, a set pressure (usually 10 MPa) is applied and held for 10 seconds, the volume (thickness) of the powder after compression is measured, and the compacted density is calculated. Compacted density = powder mass / (mold bottom area × powder thickness). The results are shown in the table below.
[0032]
[0033] The sheet-like single-crystal NFPP prepared using low-melting-point composite molten salts in Examples 1-3 exhibits high density, with measured high compaction densities (2.5~2.8 g / cm³). 3 The comparative examples of single salt (Example 2) and binary composite salt (Example 3) are not low-melting-point molten salts. They cannot provide a molten salt environment that induces the growth of lamellar single crystal morphology in the stable synthesis temperature range of NFPP. They may even hinder the growth of NFPP particles. Therefore, the NFPP compaction density obtained by comparative examples 2 and 3 is lower, indicating that the ternary composite molten salt system designed in this invention cannot achieve similar results without one of the components.
[0034] (3) The NFPP materials obtained in Examples 1-3 and Comparative Examples 1-3 were assembled into CR2032 type button cells: NFPP material, conductive carbon black, and PVDF were mixed in a mass ratio of 80:10:10 and then added to N-methylpyrrolidone. The mixture was slurried, coated onto copper foil, vacuum dried, and cut into positive electrodes with a diameter of 12 mm; metallic sodium was used as the negative electrode; and 1M NaPF6 / EC:DMC=1:1 was used as the electrolyte. The cells were charged and discharged within a voltage range of 1.8~4.2V. The results are as follows: Figure 2 , Figure 3 As shown.
[0035] Figure 2 The first charge-discharge curves of the NFPP prepared in Example 1 and Comparative Examples 1-3 at 0.1 C are shown. The results show that the first discharge specific capacity of Example 1 at 0.1 C is 111.0 mAh / g, while that of Comparative Example 1 at 0.1 C is only 91.3 mAh / g. This indicates that the lamellar single-crystal morphology of the NFPP material prepared in the examples of this invention shortens the transport path of sodium ions, which is beneficial to the specific capacity. However, the single salt and binary composite salt systems of Comparative Examples 2 and 3 cannot provide a molten salt environment to induce the growth of lamellar single-crystal morphology, and even inhibit the growth of NFPP particles. Therefore, they have a longer discharge slope region, but their specific capacity is still not as good as that of the examples.
[0036] Figure 3 The figures show the charge-discharge curves of NFPP prepared in Examples 1-3 and Comparative Example 1 at a high rate of 5 C. The sheet-like single-crystal NFPP in Examples 1-3, with its unique morphology, also exhibits excellent rate performance, with a discharge capacity of over 90 mAh / g at 5 C, which is much larger than that of the NFPP particles in Comparative Example 1.
[0037] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0038] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A method for preparing a sheet-like single-crystal sodium iron phosphate pyrophosphate cathode material, characterized in that, It includes the following steps: Sodium iron phosphate pyrophosphate precursor is mixed with a composite molten salt, calcined, and post-treated to obtain a sheet-like single-crystal sodium iron phosphate pyrophosphate cathode material; the composite molten salt includes sodium chloride, potassium chloride, and sodium sulfate, and the eutectic melting point is 530~620℃.
2. The method for preparing the sheet-like single-crystal sodium iron phosphate pyrophosphate cathode material according to claim 1, characterized in that, In the composite molten salt, the molar ratio of sodium chloride, potassium chloride and sodium sulfate is (40~60):(25~40):(5~15).
3. The method for preparing the sheet-like single-crystal sodium iron phosphate pyrophosphate cathode material according to claim 1, characterized in that, The sodium iron phosphate pyrophosphate precursor includes a sodium source, an iron source, and a phosphorus source, and the mass ratio of the sodium iron phosphate pyrophosphate precursor to the composite molten salt is 1:(0.5~5).
4. The method for preparing the sheet-like single-crystal sodium iron phosphate pyrophosphate cathode material according to claim 3, characterized in that, The sodium source is selected from at least one of sodium carbonate, sodium acetate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium oxalate, and sodium nitrate; the iron source is selected from at least one of ferric nitrate, ferric phosphate, ferrous sulfate, ferrous oxalate, and ferric fluoride; and the phosphorus source is selected from at least one of ammonium dihydrogen phosphate, orthophosphoric acid, diammonium hydrogen phosphate, and phosphoric acid.
5. The method for preparing the sheet-like single-crystal sodium iron phosphate pyrophosphate cathode material according to claim 1, characterized in that, The calcination is carried out under a protective atmosphere, with the temperature increased to 550-750°C at a heating rate of 1-5°C / min and held for 2-8 hours.
6. The method for preparing the sheet-like single-crystal sodium iron phosphate pyrophosphate cathode material according to claim 1, characterized in that, The post-processing includes washing several times with deionized water and anhydrous ethanol until no chloride or sulfate ions are detected in the washing solution, followed by vacuum drying.
7. The method for preparing the sheet-like single-crystal sodium iron phosphate pyrophosphate cathode material according to claim 6, characterized in that, The vacuum drying temperature is 80~120℃, and the drying time is 6~12h.
8. A sheet-like single-crystal sodium iron phosphate pyrophosphate cathode material, characterized in that, It is prepared by the preparation method described in any one of claims 1-7.
9. The sheet-like single-crystal sodium iron phosphate pyrophosphate cathode material according to claim 8, characterized in that, The positive electrode material has the chemical formula Na4Fe3(PO4)2P2O7, exhibits a plate-like single-crystal morphology, with a plate thickness of 10~50 nm and a compaction density of 2.5~2.8 g / cm³. 3 .
10. The application of a sheet-like single-crystal sodium iron pyrophosphate cathode material prepared by any one of claims 1-7 in the cathode of a sodium battery.